IDENTIFICATION FOR FUEL GAS IMPROVEMENT PROGRAM, CASE STUDY: PT BADAK NGL - Arief Setiawan, Mohammad
Badak LNG is a natural gas liquefaction plant located in Bontang, East Kalimantan, that has been operating since 1977 producing LNG, LPG, and hydrocarbon condensate. Badak LNG has implemented its own energy management system which has been certified by ISO 50001. The energy management system aims to improve the internal energy usage efficiency, environmental conservation, and cost saving. Based on the 2021 energy audit, it was identified that the fuel gas consumption was constantly increasing by years, in regards to the feed gas input. This indicates there is inefficient internal energy utilization indicated by excessive fuel gas consumption. The fuel gas consumption in year 2021 was around 13.3%, which is the highest recorded consumption from year 2006. Badak LNG aims to reduce fuel gas consumption to around 13.1%, to reduce gas loss, thus increasing the LNG production. Several actions were conducted to identify the root cause of the problem and the preferred solution. The root cause of the problem was evaluated by conducting focus group discussion (FGD) among related subject matter experts (SME), by using current reality tree method. Upon identifying the root causes, the next action was conducting assessment by using analytical hierarchy process (AHP) to identify the preferred solution. In this step, collaboration with SMEs is crucial to get their feedback in order to obtain the best solution that gives most optimum benefit for all attributes/criteria being assessed. The root cause of the problem was identified coming from three subjects; which are MCR (multi component refrigerant) composition not updated, manual operation in regenerator and refrigerant compressors, and improper & inefficient amine circulation. Next assessment was conducted to find five most relevant solutions by addressing the identified root causes. These solutions cover several areas of improvement: process automation, process parameter correction, and optimization of amine circulation. Afterwards, AHP was conducted by assessing these options to several consideration attributes/criteria. The AHP assessment has finally concludes three top solutions to be implemented, which are: automation of surge control in refrigerant compressors to minimize energy losses from driver steam, implementation of auto-cascade control for inlet steam to Plant-1 regenerator to minimize steam requirement, and study to identify the new optimum MCR composition to improve compressor’s efficiency. These projects shall be carried out between 1-3 years of duration.